High temperature erosion behaviour of Type AISI 446 stainless steel under the combined effect of surface modification and pre hot-corrosion - Mishra A.; Behera C.K.; Mohan S.; Mohan A.; Pradhan D. (My University, 2025)
In the present study, the effect of Surface nano crystallization (SNC), using Ultrasonic shot peening (USP), on pre-hot corrosion-erosion behaviour of Type AISI 446SS at elevated temperatures is studied. No phase change was revealed by X-ray diffraction (XRD), however, the microhardness is significantly increased in the shot peened region for USPed samples. The USPed samples were subjected to low-temperature hot corrosion (LTHC) tests under isothermal conditions for 20 h at 550, 650 and 750 ℃. The LTHC tests were carried out by spray deposition techniques using two salt mixture (Na2SO4/NaCl). Alumina (Al2O3) sand operated air-jet erosion tester was used to test the pre-hot corroded samples. The passive layer formed during LTHC suffered expulsion of metallic flakes and led to a significant change in erosion rate. © 2020 Elsevier Ltd